A Review of Social Capital as a Concept - Oladipo, Temidayo David (ABUAD Journal of Social and Management Sciences, 2023)
There is a debate about what social ‘capital’ as a concept entails. This review article is a contribution to that debate. The article explores the various ways the concept of social capital has been used in the literature. The first is that users of the concept employ it to refer to social norms and moral values and the roles they play in society. This first conceptualisation of social capital emphasises the importance that values and norms have for the effectiveness of the various forms of capital. The thinking is that if moral values and social norms are lacking in guiding the operation of the other forms of capital, little or no progress will be made in society. The next perspective is that social capital is generated in people’s daily interaction in the community. This view attaches importance to associational life in society. Finally, the paper evaluates the debate about whether social capital can be regarded as a ‘capital’, given the fact that other forms of capital are tangible while social capital is intangible. It is demonstrated in this paper that inasmuch as other types of capital are valuable because they are able to generate expected outcomes, so is social capital a ‘capital’ because it enables the achievement of certain goals in society.